2000
DOI: 10.21608/ejabf.2000.1660
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Lipid Levels and Sources on Immune Response of Nile Telapia Oreochromis Niloticus Broodstock in Winter Season

Abstract: T he present study was carried out for 120 days at Fish Research Station, belonging to the National institute of Oceanography and Fisheries at El-Kanater El Khairia The aim of work was to detect the effect of lipid sources (Poultry oil, Com oil and Linseed oil) and lipid levels (3 and 6 %) on immune response of Nile tilapia broodfish during the winter seasoa Total serum protein (TSP), total serum albumin (TSA) and Total serum globulin (TSG) parameters were used as immunoglobulin indicators. The (TSP), (TSA) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In the same trend, Shehata and Goda (2000) found that dietary lipid levels and sources affect the immune response of Nile tilapia broodstock in winter season. Attalla (2009) concluded too that oil extracts can promote growth performance and improve the physiological activities of blue tilapia (Oreochromis aureus).…”
Section: Discussionmentioning
confidence: 62%
“…In the same trend, Shehata and Goda (2000) found that dietary lipid levels and sources affect the immune response of Nile tilapia broodstock in winter season. Attalla (2009) concluded too that oil extracts can promote growth performance and improve the physiological activities of blue tilapia (Oreochromis aureus).…”
Section: Discussionmentioning
confidence: 62%
“…The obtained negative effects of AFB on fish skin, gut, liver, and kidney are reflecting the low immunity, since these organs belonging to the fish immune system (Press and Evesen, 1999) and blood proteins are non-specific immune factors (Shehata andGoda, 2000 andHussein andKobeisy, 2001). Moreover, Abdelhamid et al (2004a, b, & c) evaluated the toxicity symptoms in Oreochromis niloticus, whether on growth performance, feed and nutrients utilization, clinical, blood, and histological signs.…”
Section: Discussionmentioning
confidence: 99%